New Neotropical cunaxine species (Acari: Prostigmata: Cunaxidae) - Den Heyer, Jacob; De Castro, Tatiane Marie Martins Gomes [UNESP] (My University, 2012)
Four new Brazilian cunaxine species, namely Armascirus brasiliensis Den Heyer sp. nov., A. bahiaensis Den Heyer sp. nov., Dactyloscirus saopauloensis Den Heyer sp. nov. and Riscus austroamericanus Den Heyer sp. nov. are described and figured. A key to the new species, as well as the known species of Riscus, is provided. Copyright © 2012 Magnolia Press.
Keywords: Armascirus; Bdelloidea; Dactyloscirus; Keys; Neotropical fauna; Riscus